ANALYSIS OF FINANCIAL HEALTH, STATE-OWNED ENTERPRISES (Case Study at PT Aneka Tambang Tbk) - Zainal Arifin H. Masri (JABE (Journal of Applied Business and Economic), 2020)
This study aims to examine the financial health of State-Owned Enterprises (SOEs), particularly at PT Aneka Tambang, Tbk. The research method used is a combination of quantitative research and qualitative research methods. The quantitative method is used to calculate the financial stability indicators of PT Aneka Tambang, Tbk from year to year for six years based on the time-series data of the company's financial statements while the descriptive qualitative method is used to describe and explain narratively the financial health development of PT Aneka Tambang, Tbk. Sampling for quantitative research is done by taking time series data over the past six years that are available in the company. While qualitative research is carried out by comparing and analyzing the results of quantitative data calculations. The data analysis technique was carried out using financial ratio analysis of each indicator, then given a score, and determined the level of financial stability. Ratio analysis is carried out from year to year for the last ten years based on the time-series data obtained. The results of the calculation of ratio analysis of financial stability indicators are then compared from year to year to determine the trends in financial stability occurred